Electropolishing of nickel and cobalt in deep eutectic solvents. (4th July 2018) - Karim, W. O.; Abbott, A. P.; Cihangir, S.; Ryder, K. S.
ABSTRACT: Electropolishing is a common method for decreasing surface roughness and removing surface irregularities. In this paper the electropolishing of nickel and cobalt are successfully demonstrated in a deep eutectic solvent, comprising a 2:1 molar mixture of ethylene glycol and choline chloride. Voltammetric and electrochemical impedance studies were used to characterise the polishing mechanism and show that film formation occurs prior to polishing. Scanning electron microscopy and atomic force microscopy were used to characterise the morphology before and after polishing and 3D optical microscopy was used in-situ to observe film formation during polishing. This study shows that the impact of film formation and subsequently mass transport are responsible for electropolishing of both metals in the choline chloride-based ionic liquid.